Artificial Intelligence and Computational Intelligence Third International Conference, AICI 2011, Taiyuan, China, September 24-25, 2011, Proceedings, Part II - Deng, Hepu; Miao, Duoqian; Lei, Jingsheng; Wang, Fu Lee (Springer eBooks., 2011)
This three-volume proceedings contains revised selected papers from the Second International Conference on Artificial Intelligence and Computational Intelligence, AICI 2011, held in Taiyuan, China, in September 2011. The total of 265 high-quality papers presented were carefully reviewed and selected from 1073 submissions. The topics of Part II covered are: heuristic searching methods; immune computation; information security; information theory; intelligent control; intelligent image processing; intelligent information fusion; intelligent information retrieval; intelligent signal processing; knowledge representation; and machine learning.